Parenting Disiplin waktu Penggunaan Gawai(Gadget) Pada anak Usia Sekolah Dasar - Chasanah, Iflahathul; Ratna Utami Nur Ajizah; Irfan Jauhari (Institut Agama Islam Riyadlatul Mujahidin Ngabar (IAIRM) Ponorogo, 2023)
The development of increasingly sophisticated technology makes many conveniences in various crosses of life for humans, especially in Indonesia, where the majority of all can already take advantage of technology. However, in the facts on the ground that are happening we need to review how this technology has an impact, for example in elementary school-age children they need technology to support learning and updating science and technology but on the other hand the negative impact threatens their physical and mental development. The purpose of this writing is the need to provide information for elementary school-age children who already understand the rules and their benefits and impacts, limiting and applying time discipline in using gadgets or other technological tools. This research method is qualitative using an dercriptive qualitative approach. The results are as follows, explaining the psychological dimensions of elementary school-age children (concrete operations), how time discipline education for elementary school-age children manages learning time to play and so on, the role of parents and teachers in technology in the lives of elementary school-age children, and Benefits and impacts of Technology for elementary school-age children